The Christmas she married the playboy - Fuller, Louise (Romance author) (Harlequin presents, 2021)
"Louis Albemarle has tried to bury the pain and guilt of his father's death with his playboy antics. So when a photo of his stolen moment with figure skater Santina Somerville proves one scandal too many for his company's shareholders, Louis must contemplate the unimaginable: marriage! Marrying Louis is the only way to save Santa's pristine image. But after a past betrayal, it's not the gossip she really fears. It's the burning attraction between her and Louis that might just make resisting her convenient husband impossible..." -- Page [4] cover.